2018
DOI: 10.3390/w10091217
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Runoff Retention Performance of Extensive Green Roofs

Abstract: The runoff retention effectiveness of 10 extensive green roof (EGR) modules (100 mm substrate planted Sedum lineare Thunb.) were analyzed in Beijing for 22 rainfall events (2.4–46.4 mm) from 1 July to 30 September 2017. Differences between minimum inter-event dry periods, module scales, substrate hydraulic conductivity and depths, drainage layer types and rainfall characteristics were examined to study their correlation to the retention performance of EGRs. In general, EGRs with lower substrate hydraulic condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 27 publications
1
16
0
2
Order By: Relevance
“…Generally, the depth of precipitation event influences rainfall retention rate expressed as the percentage of rainfall retained within green roofs. In their research Gong et al reported an investigation conducted in Beijing for 22 rainfall events with use of 10 green roof modules in which lower values of stormwater retention rate were obtained in the case of heavy rains, while high retention rates were observed in the case of small storms [Gong et al, 2018]. Similar results were obtained by Burszta-Adamiak in the research conducted in Wrocław.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Generally, the depth of precipitation event influences rainfall retention rate expressed as the percentage of rainfall retained within green roofs. In their research Gong et al reported an investigation conducted in Beijing for 22 rainfall events with use of 10 green roof modules in which lower values of stormwater retention rate were obtained in the case of heavy rains, while high retention rates were observed in the case of small storms [Gong et al, 2018]. Similar results were obtained by Burszta-Adamiak in the research conducted in Wrocław.…”
Section: Resultssupporting
confidence: 53%
“…On the basis of the results from the studies available in the literature, it can be expected that the relationship between ADP and (P r ) would be much weaker if all natural rainfalls were included in the analysis regardless of their size (even those that did not cause runoff). In their research, Gong et al took into account all precipitations (including light rains that do not caused the runoff) and they established that the antecedent dry periods up to 14 days had little effect on runoff retention [Gong et al, 2018]. Schulz et al found that the retention for individual rain events showed a strong dependence on both the length of ADP and the size of the event [Schultz et al 2018].…”
Section: Resultsmentioning
confidence: 99%
“…Gong et al 3 studied the flow retention effectiveness of green roof modules and concluded that heavy rains (>25mm) significantly affect there tention performance of extensive greenroofs in then extrainyevent.…”
Section: Introductionmentioning
confidence: 99%
“…The retention and interception ability of GRs on rainwater runoff is affected by several factors, such as the type and material of the substrate layer [9,10], substrate layer thickness [11], GR scale [12], vegetation type [13][14][15], rainfall time [16], rainfall depth [17], type of drainage layer [18], water storage, whether the layer is set or not, and roof slope. Through a large number of experiments and simulation results, it can be concluded that rainfall depth as well as substrate layer thickness and material type are important parameters affecting the retention and interception capacity of the rainwater runoff of GRs.…”
Section: Introductionmentioning
confidence: 99%